OPTIMASI DIAGRAM LAYANAN PEMBELIAN DALAM MENDUKUNG MANAJEMEN HUBUNGAN PELANGGAN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
The research purpose is implementing the information communication technology (ICT) as a tool to describe purchase service process to make easy the information communication technology usage and also supporting customer relationship management (CRM). The research is also describing how to improve the advantage of efficiency, effectives, performance as well as company productivity improvement to obtained supporting customer relationship management (CRM). This research uses descriptive analytical by presenting a summary of interviews, using observation, and discuss with expert respondent using focus group discussion, literature review as well as using flowchart diagram, entity relationship diagram (ERD) and data flow diagram (DFD). The information communication technology (ICT) usage in this research by using short messages service (SMS) and design tools application in the form of a flowchart diagram, entity relationship diagram (ERD) and data flow diagram (DFD) approach used in this research were able to solve the purchase service problem and provide the best information result and computerized.